Validation of anaphylaxis in the Food and Drug Administration's Mini‐Sentinel. (5th September 2013) - Walsh, Kathleen E.; Cutrona, Sarah L.; Foy, Sarah; Baker, Meghan A.; Forrow, Susan; Shoaibi, Azadeh; Pawloski, Pamala A.; Conroy, Michelle; Fine, Andrew M.; Nigrovic, Lise E.; Selvam, Nandini; Selvan, Mano S.; et al.
ABSTRACT: Purpose: We aim to develop and validate the positive predictive value (PPV) of an algorithm to identify anaphylaxis using health plan administrative and claims data. Previously published PPVs for anaphylaxis using International Classification of Diseases, ninth revision, Clinical Modification (ICD‐9‐CM) codes range from 52% to 57%. Methods: We conducted a retrospective study using administrative and claims data from eight health plans. Using diagnosis and procedure codes, we developed an algorithm to identify potential cases of anaphylaxis from the Mini‐Sentinel Distributed Database between January 2009 and December 2010. A random sample of medical charts ( n = 150) was identified for chart abstraction. Two physician adjudicators reviewed each potential case. Using physician adjudicator judgments on whether the case met diagnostic criteria for anaphylaxis, we calculated a PPV for the algorithm. Results: Of the 122 patients for whom complete charts were received, 77 were judged by physician adjudicators to have anaphylaxis. The PPV for the algorithm was 63.1% (95%CI: 53.9–71.7%), using the clinical criteria by Sampson as the gold standard. The PPV was highest for inpatient encounters with ICD‐9‐CM codes of 995.0 or 999.4. By combining only the top performing ICD‐9‐CM codes, we identified an algorithm with a PPV of 75.0%, but only 66% of cases of anaphylaxis were identified using this modified algorithm. Conclusions: The PPV for the ICD‐9‐CM‐based algorithm for anaphylaxis was slightly higher than PPV estimates reported in prior studies, but remained low. We were able to identify an algorithm that optimized the PPV but demonstrated lower sensitivity for anaphylactic events. Copyright © 2013 John Wiley & Sons, Ltd.